Indonesian Migrant Worker (PMI) in the Agriculture Sector: Opportunities and Challenges - Susana Indriyati Caturiani; Rahayu Sulistiowati; Ayu Wulandari (The Eastasouth Journal of Social Science and Humanities, 2026)
Worker migration occurs for various reasons, one of which is economic. In migration, there are push factors and pull factors. The demand for worker in more developed countries and higher wages is pulling factors, while the lack of job opportunities and inadequate wages in the country are push factors. In recent years, the agricultural sector in Japan has become attractive to job seekers in Indonesia. This study aims to explore the opportunities for former agricultural migrants in addressing the challenge of farmer regeneration. The research employs a qualitative approach, utilizing data collection methods such as interviews, observations, and document analysis. Informants from BP3MI, SBMI, and prospective PMI were involved. The findings indicate that no such efforts have been made, and innovative policies are needed to bridge the gap between the two.